A Light Harvesting Complex-Like Protein in Maintenance of Photosynthetic Components in Chlamydomonas . Issue 4 (21st June 2017) - Zhao, Lei; Cheng, Dongmei; Huang, Xiahe; Chen, Mei; Dall'Osto, Luca; Xing, Jiale; Gao, Liyan; Li, Lingyu; Wang, Yale; Bassi, Roberto; Peng, Lianwei; Wang, Yingchun; et al.
Abstract : Msf1 is required for the maintenance of PSI and chlorophyll-binding proteins mainly under stress conditions in Chlamydomonas. Abstract: Using a genetic approach, we have identified and characterized a novel protein, named Msf1 (Maintenance factor for photosystem I), that is required for the maintenance of specific components of the photosynthetic apparatus in the green alga Chlamydomonas reinhardtii . Msf1 belongs to the superfamily of light-harvesting complex proteins with three transmembrane domains and consensus chlorophyll-binding sites. Loss of Msf1 leads to reduced accumulation of photosystem I and chlorophyll-binding proteins/complexes. Msf1is a component of a thylakoid complex containing key enzymes of the tetrapyrrole biosynthetic pathway, thus revealing a possible link between Msf1 and chlorophyll biosynthesis. Protein interaction assays and greening experiments demonstrate that Msf1 interacts with Copper target homolog1 (CHL27B) and accumulates concomitantly with chlorophyll in Chlamydomonas, implying that chlorophyll stabilizes Msf1. Contrary to other light-harvesting complex-like genes, the expression of Msf1 is not stimulated by high-light stress, but its protein level increases significantly under heat shock, iron and copper limitation, as well as in stationary cells. Based on these results, we propose that Msf1 is required for the maintenance of photosystem I and specific protein-chlorophyll complexes especially under certain stress conditions.